Arquitetura da informação no ambiente digital: avaliando as relações com o direito da propriedade intelectual - Dias, Guilherme Ataide; Vidotti, Silvana Aparecida Borsetti Gregorio (Universidade Federal da Paraíba (UFPB), 2012)
Investigates the relationship between Information Architecture in digital environments with Intellectual Property Rights. The work is justified by the need to better understand the emerging dynamics of Digital Information and Communication Law Technologies and Intellectual Property Rights. Three areas of knowledge are directly related to the study: Information Science, Law and Computer Science. The methodology used in the investigative process is aligned with the qualitative approach. With respect to the technical procedures the research is classified as bibliographic or secondary sources. The results showed that the current Brazilian legislation does not provide the adequate mechanisms necessary to protect the intellectual property rights associated to an Information Architecture project to its holders.
Information architecture in the digital environment: evaluating the relations with the Intellectual Property Rights
Keywords: Intellectual property rights; Information architecture; Information technology